Strengthening The Students' Reading Comprehension in Narrative Text With Audio-Based Asynchronous Approach as Remote Learning - Ramadhani, Reski Suci; Anugrawati, Nunung; Sangkala, Ismail (Journal of Computer Interaction in Education, 2019)
The objectives of this research were to find out the students’ reading comprehension in narrative text with audiobased asynchronous approach as remote learning at second grade students of SMP Negeri 21 Makassar. The researcher used quantitative research. The sample of this research was second grade students of SMP Negeri 21 Makassar, which consisted of 25 students. The sample was taken by using pre-test and post-test questions. Based on the findings, it was found that the students improved in teaching reading comprehension in narrative tect with an audio-based asynchronous approach as a form of remote learning. The results of this research showed that the score of pre-test was 52.6 and post-test was 78. This research also showed the value of t-test was higher than the value of t-table (T-test > T-table). The value of t-test was 7.56 and the value of t-table was 2.063. it means the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Based on the findings of the study, the researcher concluded that the audio-based asynhrnous approach as remote learning was an excellent method for enhancing students reading comprehension.